Sandwiched aramid nanofiber/Al2O3-coated polyolefin separators for advanced lithium–sulfur batteries. (February 2023) - Li, Weiwei; Yang, Bin; Pang, Ruixue; Zhang, Meiyun
Abstract: Separators have a significant impact on the safety and performance of Lithium-sulfur (Li–S) batteries. However, the current microporous polyolefin separators often suffer from inferior thermostability and electrolyte wettability. Here, a sandwiched separator based on aramid nanofibers (ANFs) and Al2 O3 nanoparticles was exploited on the base of a polyolefin separator through a facile coating process. The thin coating layer involves an entangled ANF network and Al2 O3 NPs combine high strength, toughness, desirable nanoscale porosity, excellent thermostability, and wettability, which are conducive to improving the pristine polyolefin separators. Notably, the hybrid coating layer and sandwiched construction endow the separator with the capabilities of reducing the shuttle effect and improving the electrochemical performance. The Li–S battery equipped with the obtained Al2 O3 /ANFs@PP separator delivers an enhanced first-cycle discharge capacity of 1233 mAh g -1 and 99.83% Coulombic Efficiency after 200 cycles at 0.5C. The mechanically robust, heat-resistant, wettable, and nano-porous separator could shed fresh insights into the development of advanced separators for polysulfide shuttle-free and long-life Li–S batteries. Graphical abstract: In this work, a mechanically tough and robust, heat-resistant sandwiched Al2 O3 /ANFs@PP separator with an 3D nano-porous structure, appealing wettability and improved ionic conductivity is prepared by a facile coating process, which endows the Li–S cell with enhanced cycling performance, C-rate capability as well as extremely high safety. Image 1 Highlights: A sandwiched, robust and heat-resistant Al2 O3 /ANFs@PP separator was prepared by a facile coating process. Al2 O3 /ANFs@PP separator shows a significantly improved wettability, ionic conductivity and heat-resistance . The nano-porous structure and modulus of Al2 O3 /ANFs@PP separator may resist the perforation of lithium dendrites and polysulfides. The electrochemical performance of Al2 O3 /ANFs@PP separator outperforms the majority of modified PP separators.